2022
DOI: 10.1007/s10900-022-01151-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving Health and Diabetes Self-Management in Immigrants with Type 2 Diabetes Through a Co-Created Diabetes Self-Management Education and Support Intervention

Abstract: To examine the impact of a co-created culturally sensitive diabetes self-management education and support (DSMES) intervention on the physical and mental health of immigrants with type 2 diabetes (T2D). Pre- and post-test among people with T2D whose primary language was Urdu, Arabic or Turkish (n = 97). Participants were offered a six-week intervention based on a person-centred approach using research-based dialogue tools to facilitate learning and reflection, which was developed in co-creation with immigrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Also, the fact that the HCPs were trained in cultural competence as well as dialogue and active listening with an emphasis on supporting individual change [11] may have increased the possibility of being more health literacy responsive, which is the core principle for mitigating the effects of challenged health literacy [14,37]. Our study showed that HCPs played an important role in enhancing HL levels among migrants.…”
Section: Improving Health Literacy Through Culturally Sensitive Dsmes...mentioning
confidence: 93%
See 3 more Smart Citations
“…Also, the fact that the HCPs were trained in cultural competence as well as dialogue and active listening with an emphasis on supporting individual change [11] may have increased the possibility of being more health literacy responsive, which is the core principle for mitigating the effects of challenged health literacy [14,37]. Our study showed that HCPs played an important role in enhancing HL levels among migrants.…”
Section: Improving Health Literacy Through Culturally Sensitive Dsmes...mentioning
confidence: 93%
“…This study invited participants from a culturally sensitive DSMES programme targeting migrant groups with Arabic, Turkish or Urdu as their first language and with no or limited Danish proficiency to partake in two interviews [11]. The purpose of the programme was to support health-promoting decisions and improve diabetes self-management, and covered subjects such as type 2 diabetes, insulin, diet, psychosocial issues, support, medicine, physical activity and comorbidities.…”
Section: Setting and The Culturally Sensitive Dsmes Programmementioning
confidence: 99%
See 2 more Smart Citations
“…With this alarming increase, and in order to decrease complications and diabetes-related mortality, this health problem requires a comprehensive management plan where patients should be educated to make informed decisions about diet, exercise, weight, and medications, as recommended by the American Diabetes Association (ADA) [ 7 ]. In fact, patient education has been proven to improve knowledge, dietary behaviors, and health outcomes in patients with T2D, including HbA1c and mortality reductions, lower weight and body fat, and improved quality of life [ 8 ]. Also, knowledge of diabetes was found to be associated with compliance with treatment and a decrease in complications [ 9 ].…”
Section: Introductionmentioning
confidence: 99%